Assessment of Some Risk Factors among Patients with Coronary Heart Disease - Jawad, Ahmed Kadhim (Diyala Journal of Medicine, 2018)
Background: Coronary heart disease is the most common type of heart diseases. This condition could results from a buildup of plaque inside the arteries, which decrease blood flow to the heart and raises the risk of a heart attack. The World Health Organization estimates that coronary heart disease prominent cause of death worldwide, and a number of well-characterized factors, including advanced age, genders, hypertension, diabetes mellitus, smoking and others contribute to Coronary heart disease risk development. Objective: To assess of some risk factors of patients with coronary heart disease. Patients and Methods: Hospitals based case-control study was conducted at Iraqi center for heart diseases in Ghazi Al-Hariri hospital / Medical City, Ibn-AL-Bitar cardiac surgery hospital and Ibn-AL-Nafees hospital during the periods from the 1st of November 2016 to the 30th of June 2017. A convenient sample was taken from each hospital. Typical questionnaire was used to interview 300 individuals, 100 (cases) and 200 (controls). The data collection included demographic characteristics and some risk factors of coronary heart disease. The participants were diagnosed by qualified physician and confirmed by specific laboratory and clinical tests including electrocardiogram (ECG) with the healthy controls that matched the age groups and genders. Results: This study offered that the percentage of age group is higher among (60-69) years were (12.0 %) in the cases, the number of males and females were (50, 16.7%), for each of them, according to marital status most of cases were married and educational levels the majority of cases were among institutes, colleges and above, while the occupation status were (11.3%) among house wife finally, the residence was high as (21.0%) in the urban areas, most of the risk factors were significantly associated with coronary heart diseases (P<0.05). Conclusion: Our outcomes indicated there were a significant association of modifiable risk factors (smoking, family history, diabetes mellitus, hypertension, taken meals contained high quantity fat and physical activity) for heart disease among patients with coronary heart disease.